Aspek Pertanggungjawaban Pidana Aparatur Sipil Negara Dalam Pemalsuan Tanda Tangan Korupsi - Venti Arista Lakuteru; Benny Djaja; M. Sudirman (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The forgery of signatures carried out by Alfonsius Siamloy as Regional Secretary of Southwest Maluku District (Sekretaris Daerah MBD) was related to fictitious official travel orders (SPPD) in the 2017–2018 fiscal year. This act resulted in state losses of IDR 1,500,000,000 (one billion five hundred million rupiah) based on the calculation of the Maluku Province Representative of the Financial and Development Supervisory Agency (BPKP). His actions were considered as making false or fictitious signatures. A series of signature forgeries clearly conflicted with Civil Servant (PNS) discipline. The Indonesian government has regulated this through Government Regulation Number 53 of 2010 concerning Civil Servant Discipline. Furthermore, Article 250 paragraph 2 of Government Regulation Number 17 of 2020 stipulates sanctions for civil servants committing crimes related to their positions. Forgery of signatures is also comprehensively regulated in Article 263 of the Indonesian Criminal Code (KUHP). Thus, State Civil Apparatus (ASN) who commit violations must be held criminally accountable Abstract ditulis dalam bahasa Inggris dan bahasa Indonesia (kecuali artikel yang ditulis dalam bahasa Inggris) yang berisikan isu-isu pokok, tujuan penelitian, metode/pendekatan dan hasil penelitian. Abstrak ditulis dalam dua bahasa yaitu Bahasa Inggris dan Bahasa Indonesia, maksimal 200 kata dalam bahasa Inggrisdan150 kata dalam bahasa Indonesia. Abstrak ditulis dengan Times New Roman9, spasi 1, bercetak lurus dan dengan format satu kolom. (Times New Roman 9, spasi tunggal, dan cetak miring), maksimal 1 halaman.